MEMBENTUK KARAKTER ANAK SEJAK DINI “SOSIALISASI DAN PELATIHAN” BAGI ANAK PAR GKI EMAUS KOTA SORONG - Adolfina Putnarubun; Tia Metanfanuan; Genetong Hully; Almendo Kereuway; Chelsea Gabrella Sani; Leonardus Petra Rumbewas; Zeth Momot; Bentelina Rut Fiay (Nusantara Hasana Journal, 2024)
The character of children in the modern era is greatly influenced by technological developments, their social environment, and the parenting styles they receive. According to Koesoema (2010), character formation must be carried out comprehensively through an educational approach that incorporates values, knowledge, and role models. Today's children interact not only with their surroundings but also with the challenging digital world. Therefore, shaping children's character requires an active role from various parties, including students as agents of social change. Through outreach and training activities for character development in children, the Teaching Team collaborates with students to provide character education to children and adolescents at the Emmaus Christian Church in Sorong City, using a fun, interactive, and contextual approach. The themes highlighted the importance of responsibility, courage, honesty, and the wise use of technology. This activity demonstrates the implementation of the Developmental Psychology course and our moral responsibility as academics who care about the future of the younger generation. This activity also adheres to Lickona's (1991) perspective, which states that character education must encompass the dimensions of moral knowing, moral feeling, and moral action. Therefore, our approach is not only informative but also instills values ​​and encourages concrete action in the children involved.